Julio Premat. Héroes sin atributos. Primera Edición. Buenos Aires: Fondo de Cultura Económica, 2009. Páginas: 276. - Hernández Peñaloza, Amor (2010)
Fil: Hernández Peñaloza, Amor. Universidad Nacional de Cuyo